Risk Factors for Pre-eclampsia and Eclampsia Disorders in Tertiary Care Center in Sukkur, Pakistan - Soomro, Shoaibunnisa (Cureus, 2019)
Introduction Pakistan has the third-highest incidence of maternal, fetal, and child mortality, according to a recent systemic analysis of global mortality. Thirty-four percent of maternal deaths are attributed to eclampsia among those who are admitted into tertiary care hospitals in Pakistan for delivery. In this study, we determine the risk factors associated with pre-eclampsia and eclampsia in the rural city of Sukkur, Pakistan. Methods and materials In this prospective observational study, a semi-structured questionnaire was developed to record information about maternal age, education status, parity, the status of chronic hypertension, gestational diabetes, anemia, body mass index (BMI), and history of cardiac disease of all women attending the antenatal clinic. Women diagnosed with pre-eclampsia and eclampsia were placed in a group, and their characteristics were compared with women with any pre-eclampsia and eclampsia. Results The incidence of pre-eclampsia and eclampsia was 5.6% (n=112/2212). Identified risk factors for pre-eclampsia and eclampsia included hypertension (28.7%), gestational diabetes (25.9%), anemia (14.9%), maternal age > 35 years (9.3%), BMI greater than 30 kg/m(2) (8.1%) and 35 kg/m(2) (11.7%), nulliparity (6.5%), unbooked status (i.e., lack of antenatal care; 6.4%), and low education level (5.8%). Conclusion It is important to identify the markers for pre-eclampsia and eclampsia, as they will help physicians and caregivers to reduce maternal and fetal mortality and the complications associated with it.